Effect of neuro-dynamic technique on repetitive inward ankle rolls among young Malaysian athletes - a randomized controlled trial - Vinodhkumar Ramalingam,; Viswanath Sundar,; Saju Joseph, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Inversion ankle sprains (IAS) are the most common injuries in sports and recreational activities. Incomplete rehabilitation among injured athletes may result in repetitive inward ankle rolls. Furthermore, inversion ankle sprain causes damage to the superficial peroneal nerve during repeated ankle inversion and plantar flexion. This results in positive neurodynamic tests in patients with sprained ankles. The purpose of this study was to find the effect of the neuro-dynamic technique on repetitive inward ankle rolls and compare it with standard physiotherapy on dynamic balance, pain score, peroneal longus, and tibialis anterior muscle activation response, knee range of motion (ROM), and functional ankle disability index (FADI) among young Malaysian athletes. Fourteen participants of age ranging from 17 to 35 years with repeated ankle sprains were recruited and randomized into Intervention Group A (Neurodynamic technique and Standard Physiotherapy-NDT+SP) and Intervention Group B (Standard Physiotherapy-SP). The participants of group A received NDT (4*30 s with 1-min rest) consisting of peroneal nerve mobilization began the day after the baseline and continued through the week for 3 sessions. In addition, the participants received standard physiotherapy (pain management and exercise) whereas the group B participants received only standard physiotherapy. The participants with repeated IAS were checked for FADI followed by pain score, dynamic balance (Y-balance), and knee ROM (using electro-goniometer). The peroneal longus and tibialis anterior muscle activity response was tested by Surface Electromyography (sEMG) (Noraxon Myo-Muscle) on the injured leg. The subjects of the two groups were tested on selected variables in baseline, mid, post and follow-up measurements. Repeated Measures Analysis of Variance (ANOVA) was computed to determine the interaction effects of time and between-subject factors. ANOVA results (NDT + SP) indicated that dependent variables FADI (F (1.148, 36) = 4701.14), pain score (F (1.98, 36) = 132.697), dynamic balance (F (1.409, 36) = 16.42), knee ROM (F (1.498, 36) = 62.232), peroneal longus peak activity (F (3, 36) = 25.727), and tibialis anterior peak activity (F (3, 36) = 17.563) had a significant effect (p<0.05) within the times of intervention among participants. Based on the post hoc test. FADI, pain score and knee ROM showed consistent improvement in intervention over the injured leg. The findings of this study show improvement in dynamic balance, pain score, peroneal longus and tibialis anterior muscle activation response, knee ROM, and FADI in both groups. The neurodynamic technique together with standard physiotherapy intervention shows safe and similar effects between variables. As part of the ankle rehabilitation protocol, it also recommends the neurodynamic technique to prevent repetitive IAS.